Pengembangan Permainan Ular Tangga Keyakinan dalam Peningkatan Efikasi Diri Siswa SMP - Wulandari, Devi Putri; Pravesti, Cindy Asli (Universitas PGRI Madiun, 2021)
The purpose of this research is to develop a game media of Snakes and Ladder of Faith which is effective for increasing the self-efficacy of students at SMP Negeri 2 Krian. This research and development method uses a research and development procedure with the following steps: 1) preliminary study, 2) media development, and 3) media testing. Based on the material expert's assessment, an average score of 0.46 was obtained which was categorized as quite feasible. Based on the media expert's assessment, an average score of 0.69 was obtained with the feasible category.Â The results of the user test assessment obtained results of 92.3% with the very valid category or can be used without revision. Based on the results of the limited field test, it was obtained that tcount 4.058> ttable 3.182 and Sig (2tailed) 0.027 <0.05, so that H0 was rejected and Ha was accepted.Â So it can be concluded that the game media, Snake and Ladder of Faith, is effective for increasing student self-efficacy.